Agile spectral tuning of high order harmonics by interference of two driving pulses - Schuster, Vittoria; Hilbert, Vinzenz; Klas, Robert; Liu, Chang; Tschernajew, Maxim; Bernhardt, Birgitta; Rothhardt, Jan; Limpert, Jens (Optics Express, 2021)
In this work, the experimental realization of a tunable high photon flux extreme ultraviolet light source is presented. This is enabled by high harmonic generation of two temporally delayed driving pulses with a wavelength of 1030 nm, resulting in a tuning range of 0.8 eV at the 19th harmonic at 22.8 eV. The implemented approach allows for fast tuning of the spectrum, is highly flexible and is scalable towards full spectral coverage at higher photon energies.
CRIS-Team Scopus Importer:2023-04-20